Synthesis and Characterization of the Ligand (S, S'-Bis (Benzo [d] Oxazol-2-yl) 2, 2'-((Methylenebis (4, 1 Phenylene)) Bis (Azanediyl)) Diethanethioate (BMPAE) and it's Complexes with Some Transition Metals Ions - Tariq Hussein Mgheer (Journal of Global Pharma Technology, 2017)
This study involved synthesis of ligand (S,S'-bis (benzo[d]oxazol-2-yl) 2,2'-((methylenebis(4,1-phenylene))bis(azanediyl))diethanethioate(BMPAE)by reaction in two steps. The first involved reaction between 2-Mercaptobenzoxazole with chloroacetyl chloride to get S-benzo[d]oxazol-2-yl 2-chloroethanethioate(compound-1).The second step reaction (compound-1) with 4,4'-Methylenedianiline to form S,S'-bis(benzo[d]oxazol-2-yl)2,2'-((methylenebis(4,1phenylene))bis(azanediyl))diethanethioate (BMPAE) .This ligand was characterized by melting point, FTIR,1H NMR , 13C-NMR  and elemental analysis. New chelating complexes were prepared from reaction ligand (BMPAE) with transition metal salts of Co (II), Cu (II), Cd (II), Ag (I), and Hg (II).The structures of these complexes were identified by FT-IR and UV-Vis spectra molar conductivity, melting points, elemental analysis, atomic absorption and magnetic susceptibility measurements. The FTIR spectra clearly show new bands, which were not found in ligand spectrum, while many other bands observed changes in shape, position and in intensity which are explained by the coordination with metal ions. All complexes showed tetrahedral geometry structures except Co (II), Cu (II) complexes are octahedral.Keywords: Heterocyclic, 2-Mercaptobenzoxazole, Benzoxazole complexes, Transition metal complexes.